Pengaruh Profitabilitas dan Likuiditas Terhadap Harga Saham pada Perusahaan Sektor Consumer Cyclical di Bursa Efek Indonesia Periode 2020–2024 - Ardhini Rhisnu Fadylla; Nunung Nurhasanah; Tubagus Ahmad Darodjat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of profitability (ROA) and liquidity (CR) on stock prices (PBV) in consumer cyclical sector companies on the Indonesia Stock Exchange for the 2020–2024 period. The analysis method used is multiple linear regression with classical assumption tests including normality, multicollinearity, heteroscedasticity, autocorrelation, and model feasibility tests. The descriptive statistics show that PBV has a maximum value of 147 and a mean of 3.13, ROA with a mean of 4.47, and CR with a mean of 2.47. The regression results indicate that profitability has a significant positive effect on stock prices (p=0.000, t=4.146), while liquidity has no significant effect (p=0.293, t=-1.055). The Adjusted R2 value of 0.083 indicates that ROA and CR are only able to explain 8.3% of the variation in PBV. This finding indicates that profitability is the main factor determining stock valuation in the consumer cyclical sector, while liquidity does not determine stock price changes.